EVALUATION OF TRANSPORT COMPONENT IN THE WAREHOUSE - , А. Н., Т. Ю. (Municipal economy of cities. Series: «Economy science», 2013)
A classification of approaches to the transport component. The general scheme of the supply chain, based on transport links. The models determine the evaluation of transport.